Introduction - Kerstin Dofs; Diego Mideros (Studies in Self-Access Learning Journal)
Welcome to this special issue of SiSAL Journal, where we feature papers from the last Research Network on Learner Autonomy (ReNLA) Symposium. The most recent Association Internationale de Linguistique Appliquée (or International Association of Applied Linguistics/ AILA) Congress took place in August 2021. The congress was carded to take place originally in 2020 in Groningen, The Netherlands. However, due to the COVID-19 pandemic, the congress had to be postponed and took place a year later as an online event run through the University of Groningen. As part of the congress, the ReNLA held a symposium entitled “Autonomy in the time of complexity in a changing world” on August 18th. The symposium included two featured speakers and 11 presentations (for more details, check the AILA ReNLA Newsletter linked to this special issue).